1983
DOI: 10.1104/pp.72.2.426
|View full text |Cite
|
Sign up to set email alerts
|

Photoautotrophic Growth of Soybean Cells in Suspension Culture

Abstract: Highly chlorophyllous photomixotrophic callus was visually selected from callus originating from soybean (Glycine max (L.) Merr. var. Corsoy) cotyledon. Suspension cultures initiated from this callus became photoautotrophic under continuous light with an atmosphere of 5% CO(2) (balance air). Dry weight increases of 1000 to 1400% in the 2-week subculture period have been observed. The cellular Chl content ranged from 4.4 to 5.9 micrograms per milligram dry weight which is about 75 to 90% of the Chl content in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
92
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 10 publications
0
92
0
1
Order By: Relevance
“…Unlike a leaf, however, the majority of photoautotrophic cells require elevated levels of CO2 (1-5%) for growth (1 1, 17), and the successful establishment of a cotton cell line that grows at low CO2 (660 ,uL/L) (32) led us to investigate the differences in photosynthetic carbon metabolism between cotton cells grown at the culture room ambient level of 660 ,gL/L versus 5% CO2. A comparison was also made with two lines of soybean cells that grow at 5% CO2, which have been reported previously (10,22,23 …”
mentioning
confidence: 99%
“…Unlike a leaf, however, the majority of photoautotrophic cells require elevated levels of CO2 (1-5%) for growth (1 1, 17), and the successful establishment of a cotton cell line that grows at low CO2 (660 ,uL/L) (32) led us to investigate the differences in photosynthetic carbon metabolism between cotton cells grown at the culture room ambient level of 660 ,gL/L versus 5% CO2. A comparison was also made with two lines of soybean cells that grow at 5% CO2, which have been reported previously (10,22,23 …”
mentioning
confidence: 99%
“…1). During the first 14 d of growth, the C. rubrum cell cultures grew with the same doubling time and increased in fresh and dry weight to the same extent as photoautotrophically grown soybean cells (8). Huseman et al (10) have previously reported that photoautotrophic C. rubrum cell cultures, which were grown in continuous light, increased 600% in fresh weight in 14 d and had a Chl content of 0.2 mg g-' fresh weight.…”
Section: Methodsmentioning
confidence: 89%
“…The medium contained 39.4 mm NO3-, 20.6 mm NH4+, and 1 ;tM MoO4r-with 0.1 Mm 2,4-D, but omitted sucrose and kinetin (9,16 (27). For comparative purposes, the inset to Figure 1 14 d of photoautotrophic growth for C. rubrum and soybean cells (8) (Fig. 1, D (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations